Heart rate variability alterations in Dravet Syndrome: The role of status epilepticus and a possible association with mortality risk. (January 2022) - Perulli, Marco; Battista, Andrea; Sivo, Serena; Turrini, Ida; Musto, Elisa; Quintiliani, Michela; Gambardella, Maria Luigia; Contaldo, Ilaria; Veredice, Chiara; Mercuri, Eugenio Maria; Lanza, Gaetano Antonio; Dravet, Charlotte; et al.
Highlights: Patients with Dravet Syndrome display lower heart rate variability compared to healthy controls and patients different epilepsies. Having a lower heart rate variability in DS is predicted by a recent history of SE. Compared to the literature our cohort showed better HRV and lower mortality, reinforcing a possible association between them. Abstract: Purpose: Preliminary data suggest that patients with Dravet Syndrome (DS) have a reduced heart rate variability (HRV). This seems particularly evident in patients who experienced sudden unexpected death in epilepsy (SUDEP). This study aims at confirming these findings in a larger cohort and at defining clinical, genetic or electroencephalographic predictors of HRV impairment in DS patients. Methods: DS patients followed at our Institution performed a 24h-ECG Holter to derive HRV parameters. We used as control population patients with epilepsy (PWEs) and healthy controls (HCs). In DS patients, we assessed the impact of different clinical, neurophysiological and genetic features on HRV alterations through multiple linear regression. After a mean follow-up of 7.4 ± 3.2 years since the HRV assessment, all DS patients were contacted to record death or life-threatening events. Results: 56 DS patients had a significantly reduced HRV compared to both HCs and PWEs. A recent history of status epilepticus (SE) was the only significant predictor of lower HRV in the multivariate analysis. At follow-up, only one patient died; her HRV was lower than that of all the controls and was in the low range for DS patients. Conclusion: We describe for the first time an association between SE and HRV alterations in DS. Further studies on other SCN1A -related phenotypes and other epilepsies with frequent SE will help clarify this finding. Compared to the literature, our cohort showed better HRV and lower mortality. Although limited, this observation reinforces the role of HRV as a biomarker for mortality risk in DS.